Regulation of TopBP1 oligomerization by Akt/PKB for cell survival - Liu, Kang (2006)
Regulation of E2F1-mediated apoptosis is essential for proper cellular growth. This control requires TopBP1, a BRCT (BRCA1 carboxyl-terminal) domain-containing protein, which interacts with E2F1 but not other E2Fs and represses its proapoptotic activity. We now show that the regulation of E2F1 by TopBP1 involves the phosphoinositide 3-kinase (PI3K)–Akt signaling pathway, and is independent of pocket proteins. Akt phosphorylates TopBP1 in vitro and in vivo. Phosphorylation by Akt induces oligomerization of TopBP1 through its seventh and eighth BRCT domains. The Akt-dependent oligomerization is crucial for TopBP1 to interact with and repress E2F1. Akt phosphorylation is also required for interaction between TopBP1 and Miz1 or HPV16 E2, and repression of Miz1 transcriptional activity, suggesting a general role for TopBP1 oligomerization in the control of transcription factors. Together, this study defines a novel pathway involving PI3K–Akt–TopBP1 for specific control of E2F1 apoptosis, in parallel with cyclin–Cdk–Rb for general control of E2F activities.